A4.8 The oxidative burst mediates resolution of inflammation and bone homeostasis in gout. (13th February 2015) - Schauer, C; Czegley, C; Billyy, R; Hahn, J; Rech, J; Munoz, L; Schett, G; Herrmann, M; Hoffmann, MH
Abstract : Background and objectives: The production of reactive oxygen species (ROS) during the oxidative burst is of crucial importance for the regulation of inflammation and the prevention of autoimmunity. Diminished ROS-production was reported to cause aggravation of disease in animal models of arthritis, multiple sclerosis, and psoriasis. In a murine gout model, ROS-deficient animals exhibit exacerbated and chronic inflammation and excessive new bone formation. The aim of this project is to characterise this phenotype and to elucidate its implications for human individuals with gout. Methods: Experimental gouty arthritis was induced by intraosseal injection of monosodium urate crystals (MSU) into the foot pads of wild type and Ncf1** mice that have a defective ROS-formation from phagocytes due to a mutation in a subunit of the NADPH oxidase complex 2. Paws were taken at different time points after injection and were subjected to histopathological and micro-computed tomography analyses. The role of different cell types (neutrophil granulocytes, inflammatory monocytes) and key cytokines of inflammation (IL-1, IL-6, TNF) was determined by blockade with antibodies, anakinra, or etanercept, respectively, in vivo . Human individuals with acute and chronic gout were analysed by dual energy computer tomography (DECT) for deposition of MSU and bone remodelling. Furthermore, their blood was analysed for their capacity to undergo oxidative burst and formation of neutrophil extracellular traps (NETs). Results: MSU-injected Ncf1** mice exhibited exacerbated and chronic paw inflammation with dramatic bone turnover: while on the ipsilateral site of the injection, osteolysis was predominant, large osteophytes were building on the contralateral side. In contrast, the transient inflammation developing after MSU-injection in wild type animals did not cause major changes in bone homeostasis. Depletion of neutrophils ameliorated inflammation in Ncf1** mice, but lead to chronification of arthritis in wild type mice, arguing for a role of these cells in the resolution of inflammation. Blockade on TNF, IL-1, and IL-6 all significantly dampened inflammation. In human individuals with gout, lesions and bony spurs reminiscent of those in mice could be found by DECT. Conclusion: Upon ROS-deficiency in mice, dysregulated neutrophil function and production of inflammatory cytokines results in chronic inflammation and massive bone remodelling in gouty arthritis. The pattern of bone destruction and new bone formation found in human gout suggests that similar mechanisms could be at work.